2005
DOI: 10.1093/hmg/ddi346
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies synteny mapping identifies a quantitative trait locus for bone mineral density on human chromosome Xp22

Abstract: Bone mineral density (BMD) is a complex trait with a strong genetic component and an important predictor of osteoporotic fracture risk. Here we report the use of a cross-species strategy to identify genes that regulate BMD, proceeding from quantitative trait mapping in mice to association mapping of the syntenic region in the human genome. We identified a quantitative trait locus (QTL) on the mouse X-chromosome for post-maturity change in spine BMD in a cross of SAMP6 and AKR/J mice and conducted association m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…First, a QTL was found on the mouse X-chromosome for post-maturity change in spine BMD (Szumska et al, 2006). Then, the syntenic region on human chromosome Xp22 was tested in post-menopausal women by association mapping of the human QTL, which identified a gene that encodes a nuclear protein Pirin as possibly responsible for the observed signal (Parsons et al, 2005). This study provides a valuable example that interspecies synteny can be used to identify and refine QTLs for complex traits.…”
Section: X-chromosome: Possible Culprit?mentioning
confidence: 99%
“…First, a QTL was found on the mouse X-chromosome for post-maturity change in spine BMD (Szumska et al, 2006). Then, the syntenic region on human chromosome Xp22 was tested in post-menopausal women by association mapping of the human QTL, which identified a gene that encodes a nuclear protein Pirin as possibly responsible for the observed signal (Parsons et al, 2005). This study provides a valuable example that interspecies synteny can be used to identify and refine QTLs for complex traits.…”
Section: X-chromosome: Possible Culprit?mentioning
confidence: 99%
“…In a related study, reported recently [14], we pursued the human X chromosome region corresponding to the interval expanded in Figure 6, by SNP association to BMD of the lumbar vertebrae. Using a population of 3224 postmenopausal women in the Aberdeen area, an association peak was observed within the X-chromosome interval implicated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…As detailed below, we discovered two loci that exert significant effects on this trait in adult mice; of these, one on the X chromosome was reproduced in two independent crosses. Remarkably, the latter region corresponds closely to a polymorphic locus significantly associated with vertebral BMD in postmenopausal women [14]. Further studies will be required, to determine whether other bone-related QTLs, defined in the mouse, can readily be translated to humans in advance of gene identification.…”
Section: Introductionmentioning
confidence: 99%
“…One locus derived from animal studies which has been investigated in man is a region on chromosome X which was found to be linked to post maturity change of BMD in mice [21]. Mapping of the syntenic region of chromosome X in humans using a DNA pooling strategy showed evidence of an association between two polymorphisms in the Pirin gene and lumbar spine BMD [21]. This observation remains to be replicated in other studies however.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Subsequent work showed that Darc knockout mice had reduced bone mass, and functional studies revealed that the likely mechanism by which Darc regulated BMD was through an effect on osteoclastic bone resorption, probably mediated by differences in the ability of Darc to bind chemokines in different mouse strains. One locus derived from animal studies which has been investigated in man is a region on chromosome X which was found to be linked to post maturity change of BMD in mice [21]. Mapping of the syntenic region of chromosome X in humans using a DNA pooling strategy showed evidence of an association between two polymorphisms in the Pirin gene and lumbar spine BMD [21].…”
Section: Animal Studiesmentioning
confidence: 99%